Poverty and food insecurity during COVID-19: Evidence from the COVID-19 Rural and Urban Food Security Survey (RUFSS) - June and July 2020 round - Headey, Derek D.; Goudet, Sophie; Lambrecht, Isabel B.; Oo, Than Zaw; Maffioli, Elisa Maria; Field, Erica; Toth, Russell (International Food Policy Research Institute, 2020)
The COVID-19 pandemic has triggered a global economic crisis from which very few countries will be spared. As a result of few COVID-19 cases, a relatively short-lived lockdown, and economic momentum prior to COVID-19, Myanmar is one of the few developing countries that the World Bank (2020) forecasts will not go into recession in 2020 – a very modest expansion of just 0.87 percent is forecast. A Social Accounting Matrix multiplier analysis by IFPRI projected a 0.50 percent expansion under a fast economic recovery scenario, but a 2.00 percent contraction under a slow economic recovery scenario (Diao et al., 2020). The IFPRI study projects massive declines in GDP across a range of sectors during lockdown periods, including large increases in unemployment (5 million during the lockdown period) and declines in household income of 20 to 30 percent for April to June, albeit with fast recovery thereafter.